Obstetrical Challenges in Robinow Syndrome. (22nd July 2022) - Zhang, Yingao; Casanova, Marco; Shanahan, Matthew; Sutton, V. Reid; Fox, Karin
Abstract : Robinow syndrome is a genetically heterogenous syndrome that exhibits great pleiotropy, involving skeletal genital, cardiac, and craniofacial developmental anomalies. Fertility is not always compromised, and many individuals may be able to have a healthy pregnancy. Similar to other more common skeletal dysplasias and growth disorders such as achondroplasia, there are several challenges to be addressed in managing physiologic differences that occur in the context of pregnancy, and published literature centers on pregnant people with achondroplasia. We present a patient with Robinow syndrome ( ROR2 variant), follow her clinical course through three of her pregnancies (one 20-week loss followed by two preterm cesarean deliveries at 36-week gestation), and highlight the major obstetrical considerations in her individualized care.